Pengaruh Supervisi Akademik Kepala Sekolah Terhadap Motivasi Kerja dan Kinerja Guru SD Negeri di Kabupaten Tanggamus - Eni Rita Noviyana; Tri Yuni Hendrowati; Siswoyo (Manajemen Pendidikan, 2025)
motivation and performance. Observations conducted by the researcher on the principal andteachers of the Aster 1 Cluster, which consists of public elementary schools (SD Negeri) inTanggamus Regency, aimed to assess the effectiveness of indicators for improving workmotivation and teacher performance. Through classroom teacher observations and interviews, itwas concluded that more attention is needed to improve the quality of education in schools byfocusing on teachers’ motivation and performance. Based on the above issues, the author hasprepared a thesis proposal entitled “The Influence of Principal’s Academic Supervision on WorkMotivation and Performance of Public Elementary School Teachers in Tanggamus Regency”. Theaim is to examine the influence of academic supervision by principals on teachers’ work motivationand performance. This study uses a quantitative approach with a simple regression design. Toobtain the necessary information, an ex post facto method was applied. The population in thisstudy consists of public elementary school teachers in the Aster 2 Cluster, Sumberejo District,which includes 6 schools. The sample size was determined using the Slovin formula. The researchinstruments include questionnaires on the principal’s academic supervision, work motivation,and teacher performance. Data analysis involved: (a) prerequisite tests, including normality test,homogeneity test, and multicollinearity test; and (b) hypothesis testing using simple regressionanalysis. After conducting the analysis, the research findings revealed that: (a) The principal’sacademic supervision significantly affects teachers’ work motivation, with an influence percentageof 95.3%; and (b) The principal’s academic supervision significantly affects teacher performance,with an influence percentage of 80.2%. The results of this study are also expected to serve as areference for future research, which should consider other variables that may influence teachers’ workmotivation and performance, such as pedagogical competence, communication, and other factors.